A pharmacokinetic study on red ginseng with furosemide in equine - Kwak, Young Beom; Lee, Eunkyu; Choi, Hyunjoo; Park, Taemook; Kim, Ahram; Kim, Jungon; Yoon, Jungho; Yoo, Hye Hyun (Frontiers in Veterinary Science, 2023)
Red ginseng (RG) is a popular ingredient in traditional Korean medicine that has various health benefits. It is commonly taken orally as a dietary supplement; however, its potential interactions with concomitantly administered drugs are unclear. In this study, we examined the pharmacokinetic interaction between furosemide and RG in equine plasma. Liquid chromatography with tandem mass spectrometry analysis was performed to evaluate ginsenosides in the plasma of horses after feeding them RG and furosemide and validate the results. A single bolus of furosemide (0.5 mg/kg) was administered intravenously to female horses that had consumed RG (600 mg/kg/day) every morning for 3 weeks (experimental group), and blood samples were collected from 0 to 24 h, analyzed, and compared with those from female horses that did not consume RG (control group). Four (20s)-protopanaxadiol ginsenosides (Rb1, Rb2, Rc, and Rd) were detected in the plasma. Rb1 and Rc individually showed a high concentration distribution in the plasma. The Cmax, AUC0-t, and AUC0-∞ of furosemide was significantly increased in the experimental group (p<0.05), while the CL, Vz, and Vss was decreased (p<0.05, p<0.01). These changes indicate the potential for pharmacokinetic interactions between furosemide and RG.